Rifaximin ameliorates intestinal inflammation in cirrhotic patients with hepatic encephalopathy. Issue 7 (23rd June 2021) - Tamai, Yasuyuki; Iwasa, Motoh; Eguchi, Akiko; Shigefuku, Ryuta; Kamada, Yoshihiro; Miyoshi, Eiji; Takei, Yoshiyuki
Abstract : Rifaximin (RFX) treatment can attenuate not only hyperammonemia but also Enterococcus faecalis translocation and 10‐7G values, suggesting that RFX treatment may improve intestinal inflammation and result in better overall survival.